Host Genetic Liability for Severe COVID-19 Associates with Alcohol Drinking Behavior and Diabetic Outcomes in Participants of European Descent - Wendt, Frank R; De Lillo, Antonella; Pathak, Gita A; De Angelis, Flavio; , COVID-19 Host Genetics Initiative; Polimanti, Renato (Frontiers in Genetics, 2021)
Risk factors and long-term consequences of COVID-19 infection are unclear but can be investigated with large-scale genomic data. To distinguish correlation from causation, we performed in-silico analyses of three COVID-19 outcomes (N>1,000,000). We show genetic correlation and putative causality with depressive symptoms, metformin use (genetic causality proportion (gĉp) with severe respiratory COVID-19=0.576, p=1.07x10-5 and hospitalized COVID-19=0.713, p=0.003), and alcohol drinking status (gĉp with severe respiratory COVID-19 =0.633, p=7.04x10-5 and hospitalized COVID-19=0.848, p=4.13x10-13). COVID-19 risk loci associated with several hematologic biomarkers. Comprehensive findings inform genetic contributions to COVID-19 epidemiology, molecular mechanisms, and risk factors and potential long-term health effects of severe response to infection.